Liberal Way of Life as a Political Philosophical Problem: Review of the Book: Lefebvre, A. (2024). Liberalism as a Way of Life. Princeton; Oxford: Princeton University Press, 285 p. - Vladimir A. Gutorov; Aleksandr A. Shirinyants (RUDN Journal of Political Science)
It is no coincidence that the book by Alexandr Lefebvre, professor of political science and philosophy at the University of Sydney, has caused a rather complex range of impressions in the Western academic world and political journalism immediately after its publication by Princeton University Press. Scientists were undoubtedly attracted and at the same time somewhat puzzled by the author’s rather unconventional interpretation of the phenomenon of liberalism. Judging by the context of A. Lefebvre’s earlier works, his turn to the problems of liberalism seems quite unexpected. The reason for the scientist’s sudden turn to the topic of liberalism is caused by a number of theoretical considerations of a political and philosophical nature. The central role in A. Lefebvre’s “strategy” is played by the concept and image of the “Christian kingdom” (Christendom), borrowed from biblical political rhetoric. The “liberal kingdom” (Liberaldom) is, according to A. Lefebvre, a mixture of liberalism and other ideologies and systems, including capitalism (with its individualism, materialism and instrumentalism), democracy (with its latent populism), nationalism and internationalism (with their patriotism and often chauvinism), meritocracy (with its calculations of value and reward), as well as overtly illiberal forces. This character of Lefebvre’s argumentation can hardly be perceived positively by many real and potential allies of liberalism. In general, A. Lefebvre’s book differs from many apologetic works, first of all, in that the apology for the liberal way of life presented in it spontaneously acquires an overtly conservative shade.